Analisis Pentingnya Pendidikan Inklusi untuk Anak Berkebutuhan Khusus di SDN Poris Gaga 2 Kota Tangerang - Nurfadillah, Septy; Ulfah, Marifatul; Fitriyani, Dewi; Nikmah, Siti Zaedatun; Syifa, Umi Nur; Kauniyah, Nadhiyatul; Nurfalah, Kholis (Lembaga Yasin AlSys, 2022)
This study aims to find out the fact that there are still many children with special needs in Indonesia who have not received education, so a solution is carried out for children with disabilities to obtain education in public schools in elementary schools that have implemented inclusive learning. The Importance of Inclusive Education for Children with Special Needs at SDN Poris Gaga 2 Tangerang City. This researcher is a type of qualitative researcher. The instruments used are observation, interviews and documentation. Those who are different because they have a disability, are marginalized, do not get a touch of affection and mean social contact are not even recognized. The government is in the midst of inclusive education, where inclusive education is able to place all children (normal children and children with special needs) in the community which is an effort not to separate them from normal society.